GROWTH OF JUVENILE GREEN SNAIL (Turbo marmoratus) CULTURED IN CAGES PLACED AT DIFFERENT DEPTHS - Dwiono, S. A.P.; Setyono, D. E.D. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2006)
This research was part of successive studies on culture techniques of juvenile green snail (Turbo marmoratus). This study was carried out for 14 weeks in coastal waters of Morella, Ambon Island. Three cages were placed at depths of 0 m, 4 m and 8 m below mean sea level. Each cage had a bottom area of 0.81 m2 and was stocked with 20 green snail juveniles of 40-50 mm shell diameter. During the first 4 weeks, juveniles reared at 0 m deep showed lowest instantaneous growth, while those reared at 8 m deep attained highest instantaneous growth. The instantaneous growth decreased significantly over 6 weeks for juveniles reared at 4 m and 8 m deeps. Over 14 weeks, juveniles reared at 8 m deep had higher daily growth than those at 0 m deep. It is recommended that to grow green snail juveniles at 8 m deep without any food complement, the substrates (coral nibbles) in the cages need to be renewed every 4 weeks with ones covered with microalgae.